Aggressive behavior: an alternative model of resting heart rate and sensation seeking. Issue 1 (31st August 2013) - Wilson, Laura C.; Scarpa, Angela
<x xml:space="preserve">Abstract</x> Low resting heart rate is a well‐replicated biological correlate of aggression, and sensation seeking is frequently cited as the underlying causal explanation. However, little empirical evidence supports this mediating relationship. Furthermore, the biosocial model of violence and social push theory suggest sensation seeking may moderate the relationship between heart rate and aggression. In a sample of 128 college students (82.0% White; 73.4% female), the current study tested a moderation model as an alternative relationship between resting heart rate and sensation seeking in regard to aggression. Overall, the findings partially supported an interaction effect, whereby the relationship between heart rate and aggression was moderated by sensation seeking. Specifically, the oft‐noted relationship between low resting heart rate and increased aggression was found, but only for individuals with low levels of sensation seeking. If replication supports this finding, the results may better inform prevention and intervention work. Aggr. Behav. 40:91–98, 2014. © 2013 Wiley Periodicals, Inc.